Beating burnout at work : why teams hold the secret to well-being and resilience - Davis, Paula (Psychologist) (Wharton School Press, 2021)
A first-of-its-kind, science-backed toolkit takes a holistic approach to burnout prevention by helping individuals, teams, and leaders build resilience and thrive at work. Burnout has become one of the most talked about workplace topics, and its impact is far-reaching. The 24/7 pace of work, constant demands, and scant resources can easily put busy professionals on a path to burnout, a cycle that has only accelerated during the COVID-19 pandemic. Burnout affects the health and well-being of the entire organization, yet most attempts to help focus on quick-fix strategies aimed at individuals. Something is missing. In Beating Burnout at Work: Why Teams Hold the Secret to Well-Being and Resilience, Paula Davis, founder of the Stress & Resilience Institute, provides a new framework to help organizations prevent employee burnout. Davis's research-driven, fast-reading, and actionable book is the first of its kind to explore a new solution to the burnout problem at work: a comprehensive approach focused on building the resilience of teams of all sizes. Davis argues that teams, and their leaders, are uniquely positioned to create the type of cultures that are needed to prevent burnout. Solving the burnout puzzle requires a systemic approach. In Beating Burnout at Work, Davis offers an actionable method to help leaders create cultures of well-being and resilience in their organizations.